A comparative study on energy saving and economic efficiency of different cooling terminals based on exergy analysis. (July 2020) - Li, Zhengrong; Zhang, Dongkai; Chen, Xiangyun; Li, Cui
Abstract: The efficiency of air conditioning terminal has become a key factor for energy saving in low energy buildings because the significant reduce of sensible heating and cooling load. This paper presents an investigation for the optimal scheme of air conditioning terminal in ultra-low energy buildings. The exergy method is applied to investigate the energy efficiency and cost-effectiveness potential for the solution of air conditioning terminal in ultra-low energy buildings in hot summer and cold winter region of China. Theoretical model for energy conservation is proposed, and cost equation is used to evaluate economic efficiency. The effects of climate and system parameter on energy efficiency of different air conditioning terminals are also investigated. The results showed that the exergy efficiency and exergy consumption saving rate of radiant cooling terminal resulted in 30% higher than that of fan coil, respectively. The radiant cooling terminal has better adaptability to climate compared with the fan coil. It is crucial for radiant cooling system to increase supply water temperature and decrease the temperature difference because a wide range of naturally available exergy sources can be used. Furthermore, the radiant cooling terminal yields lower exergy unit prices and makes sound economic sense throughout the life cycle than the fan coil. A new approach to evaluate the energy and economic efficiency is introduced and applied to analysis the optimal air conditioning solution for ultra-low energy buildings. Highlights: An optimal air conditioning solution in ultra-low energy buildings is analyzed. Exergy analysis is applied for energy and economic efficiency comparing. The effect of climate and system parameter on exergy efficiency is investigated. Cost equation is used to evaluate economic efficiency.